Resilience of Flat Slab Structures in Different Phases of Progressive Collapse - Qian, Kai (2016)
With a spate of high-profile structural collapses leading to severe casualties and economic loss in recent history, there has been a growing interest in understanding the behavior of building structures in resisting progressive collapse. While many experimental and analytical studies have been conducted, they have mainly been focused on beam-column or beam-column-slab frames. This study, on the other hand, focuses on the behavior of reinforced concrete (RC) flat slab structures, as they are also highly vulnerable to collapse. This is especially so given that: 1) flat slab structures may have insufficient stiffness to redistribute the loads initially resisted by the lost column; and 2) the residual load-resisting capacity of remaining structures may not be able to sustain existing service loads after removal of several columns. Two series of multi-panel RC flat slab substructures were tested with two different loading rigs to study the load redistribution behavior and residual resisting capacities of flat slab structures when two different phases of collapse are concerned. The main test results such as load displacement response, crack pattern, failure modes, and local strain gauge readings were presented and discussed. Based on test results, a series of further analyses were carried out to elucidate the effects of each design parameter.